How social media algorithms influence the way users decide – Perspectives of social media users and practitioners - Poleac, Gabriela; Gherguț-Babii, Alexandra-Niculina (Technium Social Sciences Journal, 2024)
This study dives into the perspectives of social media users and practitioners on the impact of social media algorithms, with a focus on data curation, real-time personalization, and FOMO (fear of missing out). This research, which was conducted through two exploratory focus groups, uncovered the nuanced dynamics underlying users’ engagement with algorithms. The study of the literature emphasizes the importance of algorithms as gatekeepers in affecting online interactions, decision-making, and information intake. Our work, which is based on information foraging theory, reveals how algorithms, through characteristics such as FOMO, personalized content distribution, and the appearance of choice, profoundly shape users’ decision-making processes in the digital arena. Understanding these distinguishing characteristics reveals the psychological and behavioral elements that contribute to consumers’ continuous reliance on social media platforms. This study adds to the larger conversation about the societal implications of algorithmic influence and provides useful insights for researchers, practitioners, and policymakers navigating the ever-evolving landscape of digital interactions.